2022
DOI: 10.1007/s11274-022-03367-5
|View full text |Cite
|
Sign up to set email alerts
|

Acinetobacter baumannii, Klebsiella pneumoniae and Elizabethkingia miricola isolated from wastewater have biodegradable activity against fluoroquinolone

Abstract: Ciprofloxacin (CIP) and levofloxacin (LEV), widely used fluoroquinolone antibiotics, are often found in sewage from the sewage treatment plants and marine environment. In this study, CIP and LEV biodegrading bacterial consortia were obtained from industrial wastewater. Microorganisms in these consortia were identified as Acinetobacter baumannii (A. baumannii), Klebsiella pneumoniae (K. pneumoniae) and Elizabethkingia miricola (E. miricola). The impacts of the critical operating parameters on the elimination of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 76 publications
0
2
0
Order By: Relevance
“…Ciprofloxacin and levofloxacin are fluoroquinolone antibiotics that are widely used in hospitals and frequently present in wastewater treatment plants and marine environments. It has been demonstrated that Klebsiella pneumoniae strains obtained from industrial wastewater exhibit biodegradation capabilities toward quinolone drugs [18]. Additionally, newly isolated Klebsiella pneumoniae strains could produce self-secreted biosurfactants that enhance the solubility and bioavailability of xylene, facilitating the biodegradation of hydrophobic and toxic gases [19].…”
Section: Discussionmentioning
confidence: 99%
“…Ciprofloxacin and levofloxacin are fluoroquinolone antibiotics that are widely used in hospitals and frequently present in wastewater treatment plants and marine environments. It has been demonstrated that Klebsiella pneumoniae strains obtained from industrial wastewater exhibit biodegradation capabilities toward quinolone drugs [18]. Additionally, newly isolated Klebsiella pneumoniae strains could produce self-secreted biosurfactants that enhance the solubility and bioavailability of xylene, facilitating the biodegradation of hydrophobic and toxic gases [19].…”
Section: Discussionmentioning
confidence: 99%
“…Acinetobacter sp., Klebsiella sp., and Elizabethkingia sp. efficiently biodegrade ciprofloxacin and levofloxacin [ 77 ]. Rhizobacter gummiphilus , found at all three sites, participates in the degradation of rubber, a component of tyres and surgical gloves [ 45 ].…”
Section: Discussionmentioning
confidence: 99%
“…This phenomenon has been often described as an adaptation to improve stress tolerance since several studies demonstrated that although toxic substances may inhibit microbial growth, the long-term exposure to sub-inhibitory concentrations of a toxic substance may result in an improvement in microbial ability to grow in the presence of these substances or even metabolize them. 57 Shaker et al 58 reported that Acinetobacter baumannii can degrade fluoroquinolones (CIP and LEV). Kim et al 59 demonstrated that the previous adaptation of E. coli to formic acid also resulted in a reduction in the doubling time.…”
Section: Effect Of Ecs Exposure On a Calcoaceticus Growth Ratementioning
confidence: 99%